2019
DOI: 10.1111/bcp.13844
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin and pregabalin to treat aggressivity in dementia: a systematic review and illustrative case report

Abstract: AIMSThe prevalence of dementia is rising as life expectancy increases globally. Behavioural and psychological symptoms of dementia (BPSD), including agitation and aggression, are common, presenting a challenge to clinicians and caregivers. METHODSFollowing PRISMA guidelines, we systematically reviewed evidence for gabapentin and pregabalin against BPSD symptoms of agitation or aggression in any dementia, using six databases (Pubmed, CINHL, PsychINFO, HealthStar, Embase, and Web of Science). Complementing this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 87 publications
1
30
0
Order By: Relevance
“…However, whether the effects of these drugs are helpful for long-term control of HIDA domain symptoms is unclear. The evidence for other pharmacological approaches either does not support their use, as is the case for VPA, or is in its infancy, as is the case for AVP-923 (Fhager et al, 2003; Weiner et al, 2005; Birks, 2006; Howard et al, 2007; Kyomen et al, 2007; Ballard et al, 2009; Ng et al, 2009; Rodda et al, 2009; Sommer et al, 2009; Mowla and Pani, 2010; Lockhart et al, 2011; Gallagher and Herrmann, 2014; Cummings et al, 2015; Suzuki and Gen, 2015; Baillon et al, 2018; Kongpakwattana et al, 2018; Sherman et al, 2018; McShane et al, 2019; Supasitthumrong et al, 2019). Overall, substantial improvement is needed to increase the efficacy and reduce the side effects of pharmacotherapies for HIDA domain symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether the effects of these drugs are helpful for long-term control of HIDA domain symptoms is unclear. The evidence for other pharmacological approaches either does not support their use, as is the case for VPA, or is in its infancy, as is the case for AVP-923 (Fhager et al, 2003; Weiner et al, 2005; Birks, 2006; Howard et al, 2007; Kyomen et al, 2007; Ballard et al, 2009; Ng et al, 2009; Rodda et al, 2009; Sommer et al, 2009; Mowla and Pani, 2010; Lockhart et al, 2011; Gallagher and Herrmann, 2014; Cummings et al, 2015; Suzuki and Gen, 2015; Baillon et al, 2018; Kongpakwattana et al, 2018; Sherman et al, 2018; McShane et al, 2019; Supasitthumrong et al, 2019). Overall, substantial improvement is needed to increase the efficacy and reduce the side effects of pharmacotherapies for HIDA domain symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Other antiepileptic drugs are much less well studied, usually having only case reports or small RCTs to support or discourage their use. For instance, gabapentin has a handful of case reports suggesting that it may be effective in treating agitation and aggression in dementia but has no prospective cohorts or RCTs (Supasitthumrong et al, 2019). Lamotrigine similarly has low-quality evidence from a retrospective chart review and open-label clinical trial showing that it may reduce agitation in dementia (Ng et al, 2009; Suzuki and Gen, 2015).…”
Section: Pharmacological Treatment Approachesmentioning
confidence: 99%
“…In a retrospective design of cases Cooney et al [80] found that low-dose gabapentin could be effective in treatment of aggression in patients with vascular dementia. A recent systematic review by Supasitthumrong et al [81] about evidence of gabapentin and pregabalin in the management of NPS found low-evidence for the use of these medications for that matter. There are case series showing positive results with gabapentin, however there are no randomized controlled trials [71].…”
Section: Gabapentin Lamotrigine and Oxcarbazepinementioning
confidence: 99%
“…Blockade of presynaptic voltage-gated calcium channels containing α2δ1-subunits to reduce excitatory neurotransmitter release has become an increasingly popular pharmacological principle that is employed for a variety of diseases and conditions 1. The gabapentinoids, gabapentin and pregabalin, as the currently clinically available compounds in this class of medications are hence being used or have been trialed for management of for instance anxiety and bipolar disorders, behavioral and psychological symptoms of dementia (BPSD), chronic pruritus, epilepsy, hiccups, hot flashes, refractory cough, restless legs syndrome, spinal muscular atrophy, substance abuse disorders, and tinnitus 24. They are particularly popular in pain medicine and are therefore employed for the treatment of fibromyalgia, headaches, osteoarthritis, and post-operative as well as peripheral and central neuropathic pain 2,5,6.…”
Section: Introductionmentioning
confidence: 99%